Synthesis of titanium diboride by electric arc plasma in air; Materials Chemistry and Physics; Vol. 328 - Svinukhova A. A. Arina Andreevna; Pak A. Ya. Aleksandr Yakovlevich; Povalyaev P. V. Pavel Vadimovich; Nikitin D. S. Dmitry Sergeevich; Nassyrbayev (Nasyrbaev) A. Artur; Korchagina A. P. Anastasiya Pavlovna; Li Yu. V. Yuliya Vladimirovna (2024, 2024)
Title screen